Extrinsically reinforced hybrid speciation within Holarctic ermine (Mustela spp.) produces an insular endemic. Issue 4 (1st February 2021) - Colella, Jocelyn P.; Frederick, Lindsey M.; Talbot, Sandra L.; Cook, Joseph A.
Abstract: Aim: Refugial isolation during glaciation is an established driver of speciation; however, the opposing role of interglacial population expansion, secondary contact, and gene flow on the diversification process remains less understood. The consequences of glacial cycling on diversity are complex and especially so for archipelago species, which experience dramatic fluctuations in connectivity in response to both lower sea levels during glacial events and increased fragmentation during glacial recession. We test whether extended refugial isolation has led to the divergence of genetically and morphologically distinct species within Holarctic ermine ( Mustela erminea ), a small cosmopolitan carnivore species that harbours 34 extant subspecies, 14 of which are insular endemics. Location: Holarctic. Methods: We use genetic sequences (complete mitochondrial genomes, four nuclear genes) from >100 ermine (stoats) and geometric morphometric data for >200 individuals (27 of the 34 extant subspecies) from across their Holarctic range to provide an integrative perspective on diversification and endemism across this complex landscape. Multiple species delimitation methods ( iBPP, bPTP ) assessed congruence between morphometric and genetic data. Results: Our results support the recognition of at least three species within the M. erminea complex, coincident with three of four genetic clades, tied to diversification in separate glacial refugia. We found substantial geographic variation within each species, with geometric morphometric results largely consistent with historical infraspecific taxonomy. Main conclusions: Phylogeographic structure mirrors patterns of diversification in other Holarctic species, with a major Nearctic‐Palearctic split, but with greater intraspecific morphological diversity. Recognition of insular endemic species M. haidarum is consistent with a deep history of refugial persistence and highlights the urgency of mindful management of island populations along North America's North Pacific Coast. Significant environmental modification (e.g. industrial‐scale logging, mining) has been proposed for a number of these islands, which may elevate the risk of extinction of insular palaeoendemics.